2011
DOI: 10.1080/07418825.2011.583931
|View full text |Cite
|
Sign up to set email alerts
|

Re-Examining the Functional Form of the Certainty Effect in Deterrence Theory

Abstract: In this paper we explore the functional form of the risk-certainty effect for deterrence. Using a sample of serious youth offenders, we first estimate a simple linear model of the relationship between the perceived certainty of punishment and self-reported offending. Consistent with previous literature we find evidence of a moderate deterrent effect. We then examined whether, consistent with a linear model, the effect of perceived risk is truly constant at different ranges of the risk continuum. Estimating a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 63 publications
3
40
0
Order By: Relevance
“…Precisely how the independent variables affect the dependent variables (i.e., less crime) is unclear (however, cf. Loughran et al 2012). Self-awareness theory provides a mechanism that fits with the observed.…”
Section: Theoretical Implicationsmentioning
confidence: 60%
See 1 more Smart Citation
“…Precisely how the independent variables affect the dependent variables (i.e., less crime) is unclear (however, cf. Loughran et al 2012). Self-awareness theory provides a mechanism that fits with the observed.…”
Section: Theoretical Implicationsmentioning
confidence: 60%
“…Deterrence theory offers the requirement of a heightened level of appreciation that not only is someone observing our behavior but that the observing entity will punish us for transgressions. At a high level of abstraction, there is ample evidence that the perceived certainty of punishment is causally associated with less rule-breaking (Ariel and Partridge 2016;Bushway and Reuter 2008;Lochner 2003;Loughran et al 2012;McCord and Conway 2002;Nagin 2013a;Nagin 2013b;Paternoster 2010;Pratt et al 2006;but cf. Berk and MacDonald 2010;Tonry 2008;Wikström and Treiber 2007).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For instance, two recent studies using an offender-based sample suggest how the conceptualization of risk perceptions in individuals may be thought of as another type of individual difference by which deterrence mechanisms may vary. In the first, Loughran et al (2011c) observed a threshold risk level, or a tipping effect, above which higher levels of perceived risk were associated with a reduction in offending (as predicted by deterrence theory) but below which no such relationship existed. They reasoned that sanction risk threats below this threshold were overwhelmingly deemed to be noncredible by potential offenders and thus were not considered in their decision-making calculus.…”
Section: Heuristic Biasesmentioning
confidence: 92%
“…As Loughran et al (2012b, p. 714) explained, Bcertainty effects are predictably non-linear, [and] the prevailing detection probability before change occurs becomes a key moderator of certainty effects and a key consideration in policy formation. ^Loughran et al (2012b) came the closest to empirically scrutinizing this effect, using subject-level data (as opposed to aggregated data); they show evidence of a Btipping effect^, whereby perceived risk deters only when it reaches a certain threshold and a substantially accelerated deterrent effect occurs for individuals at the high end of the risk continuum. This is unsurprising, because the phenomenon is well acknowledged in psychology and in economics in the framework of Bdiminishing marginal sensitivity^ (Stevens 1957;see also Chamlin 1991;Logan 1972;Tittle and Rowe 1974).…”
Section: Quantifying the Certainty Of Apprehensionmentioning
confidence: 99%
“…Yet there has been little attention to operationalizing subjective threat in experimental work. Nagin (2013a, b), Loughran et al (2012b), and more recently Nagin et al (2015) have modeled the necessary conditions in which deterrence exerts an effect on decision-making. Yet how much of a threat, with what immediacy and what kind of social control has generally been untested.…”
Section: Introductionmentioning
confidence: 99%